IMPROVEMENT OF THE 5G NETWORK CORE WITH THE PURPOSE OF INCREASING THE LEVEL OF COMMUNICATION SECURITY - Odarchenko, Roman; Hryhorenko, Dmytro; Fesenko, Vladyslav; Drofa, Tetiana (Science-based technologies, 2023)
The use of modern technological solutions for the construction of radio networks for various purposes is an indisputable requirement of modernity. But in this situation, the issues of network security in general and the security of the government radio communication network come to the fore. In addition, indicators of the quality of service for subscribers of government communication networks are also very important at the moment. Therefore, it was necessary to conduct a meaningful analysis of the possibilities of using modern cellular communication networks to determine the possibilities of building government radio communication networks on their basis. As a result of the work, an analysis of the main requirements for 5G cellular communication networks was carried out, in particular, regarding their reliability, data transmission speed, delay, mobility support and other characteristics important for the user, and a study of the main requirements for modern government radio communication networks was carried out. For this purpose, the classification of services, which are planned to be provided to subscribers of modern and promising government radio communication networks in Ukraine, was expanded. New requirements were formed for these new services, which include user requirements related to quality of service (user experience) and functional requirements. It was shown that, thanks to the use of the principles of Network Slicing, the physical infrastructure is divided into virtual platforms, each of which uses the resources and technologies that are best suited for solving its tasks. This makes it possible to build more secure, isolated layers of the 5G network. An improved architecture of the government radio communication network based on 5G technology was also presented. Thanks to the capabilities provided by 5G, encryption and control of the integrity of signaling and user traffic will be carried out, which is the most important thing for government radio communication networks. Also, 5G makes it possible to isolate different layers of the Network slicing architecture and define its own security levels for the government radio communication layer. A secure government communication session establishment procedure was developed for this architecture.